Efeito das sementes de Linum usitatissimum L. var. humile (Mill.) Pers. (linhaça marrom) no aparelho reprodutor de ratas ovariectomizadas - GONÇALVES, Elaine Mendes (2014)
The hormone replacement therapy is the most effective way for the treatment of conditions related to post-menopause, but is related to the presence of undesirable effects. In this situation, safer alternatives have been investigated for the treatment of menopausal symptoms arising, such as the use of phytoestrogens. Seeds of Linum usitatissimum L. (flaxseed) are rich in lignan precursor, which is converted to substances which are structurally similar to estrogen. This study evaluates the effect of the hydro alcoholic extract of the seeds of L. usitatissimum on the reproductive tract of ovariectomized female Wistar rats. The seeds were crushed and remacerated and three times in 70% ethanol in the ratio 1:3 (v/v) for 24 hours to obtain the extract. Adult rats (80 days) from Rattus norvegicus species, divided into 6 groups (n = 5-6) were used: sham operated (FO) and ovariectomized (OVR) administered distilled water/3% cremophor (0.1 ml/100g, v. o.); estradiol benzoate (BE), ovariectomized treated with estradiol benzoate at a dose of 10 μg/kg (s. c.) and three ovariectomized groups treated with the extract of L. usitatissimum at doses of 100 mg/kg (LIN100), 250 mg/kg (LIN250) or 500 mg/kg (LIN500). The rats were ovariectomized and 21 days after surgery, received daily treatments, for two months, when it was rated the estrous cycle, body weight and food consumption. At the end of this period, blood was collection and subsequent biochemical and hormonal analyzes, and organ weighing, uterine reactivity and uterus, vagina and breasts histology. In the analysis of the estrous cycle, the OVR group had a higher frequency in the diestrus stage during the 2 months. The LIN100 group showed up 100% in diestrus and LIN250, 94.5% (1st month) and 93.5% (2nd month). At the highest dose tested (LIN500 group), flaxseed showed in the 2nd month of treatment, 14.3% of pro-estrus and diestrus 61.9%. The BE group reached 100% of estrus in the 2nd month. Ovariectomy induced body weight gain in OVR group (19.6%) which was prevented in the groups LIN and BE. Moreover, the groups treated with the extract did not alter uterus weight in relation to OVR, which showed a decrease of 83.4% compared to the FO. However, in BE, were increased by 80.5% the uterus weight. Ovariectomy induced intra-abdominal fat gain which was reduced to 47.9% in the LIN500 group 35.5% and 45.8% in BE group. In biochemical analyzes no differences between the groups was observed. In hormone dosage, OVR group decreased by 75.3% in estradiol compared to FO, whereas in the groups treated with the extract showed no differences compared to OVR. In relation to progesterone, there was no difference between groups. Uterine responsiveness to carbachol, PGF2α and oxytocin was decreased with ovariectomy and L. usitatissimum extract did not alter this effect. Histomorphometric analysis of the uterus, LIN500 group showed a significant increase in the luminal epithelium of the uterus in 12.8%, when compared to the OVR group. The other parameters did not differ, as well as the breasts histomorphometry. Therefore, the hydro alcoholic extract of L. usitatissimum has potential as an alternative to therapy in postmenopausal women, as it showed cytological parameters and on adipose tissue effects, without stimulating breast and endometrial tissues.